Study protocol: how does parental stress measured by clinical scales and voice acoustic stress markers predict children’s response to PTSD trauma-focused therapies? - Philippe Robert; Arnaud Fernandez; Florence Askenazy; Morgane Gindt; Ophelie Nachon; Alexandra König; Radia Zeghari; Hali Lindsay (BMJ Open, 2023)
Introduction Post-traumatic stress disorder (PTSD) symptoms in youth are influenced by parental anxiety and stress. When parents have high levels of stress or have developed PTSD themselves, children tend to show more anxiety symptoms. Parental stress can affect the severity of children’s PTSD and lower the success of recovery. However, the influence of parental stress on the effectiveness of trauma-focused therapies (eye movement desensitisation and reprocessing and cognitive behavioural therapy) has not yet been investigated to our knowledge. Hence, we will measure parental stress (using both validated scales and vocal acoustic markers) and investigate how it influences children’s PTSD recovery.Method and analysis Sixty children between the ages of 7 and 15 years who experienced type 1 trauma will be recruited at the Nice Pediatric Psychotrauma Center in France. We plan to measure stress using two different approaches. We will ask parents to answer validated scales of stress and mood in general. Stress will also be measured using vocal acoustic markers. Parents will be recorded while narrating their child’s trauma and during the narrative of a positive and neutral recall of events. Child participants will have to complete anxiety, PTSD and depression scales before the beginning of the trauma-focused therapy and after 3 months of treatment.Linear mixed effects models and differential statistics, such as significance testing corrected for multiple testing, will be used to determine the validity of speech features for the proposed hypotheses. Repeated measures analysis of variance will be performed on the clinical scales scores according to parental stress. Correlations will be performed between clinical scales of parents and children according to time of assessment.Ethics and dissemination This study was approved by the Committee for the Protection of Individuals of the University of Nice Sophia Antipolis (CERNI) on 21 February 2022, under the number CER2022-015.All participants will be informed that this is an observational study and their consent taken prior to the experiment. Participants will be informed that they can withdraw from the study at any time and that it would not affect the care provided.Trial registration number CER AVIS n° 2022-015.